Discourses of purity in transcultural perspective (300-1600) - Bley, Matthias; Jaspert, Nikolas; Köck, Stefan (Dynamics in the history of religions, 2015)
This volume comprises fifteen articles on the differing functions that purity, impurity, pollution and related categories could fulfil in Asian and European religions and societies of the 3rd to 17th century c.E. They focus processes of religious demarcation and transfer